ANALISIS PENERAPAN CHARACTER, CAPACITY, CAPITAL, COLLATERAL, AND CONDITION (5C) PADA BAGIAN PEMBERIAN PINJAMAN DI PT BPR SINDANG BINAHARTA KOTA LUBUKLINGGAU - Muhammad Effendi (LPPM UNIVERSITAS BINA INSAN, 2020)
This study aims to determine the analysis of the application of character, capacity, capital, collateral, and condition (5c) in the loan distribution section of PT BPR sindang binaharta, Lubuklinggau city. The data analysis technique in this study is guided by the provision of credit in the principles of implementing character, capacity, capital, collateral, and conditions (5c). Based on the results of the discussion in the previous chapter, it can be concluded that: the application of character, capacity, capital, collateral, and condition (5C) in the lending section at PT BPR Sindang Binaharta Lubuklinggau City has implemented steps taken by conducting an initial interview process and on the spot to field and in the end the main director who determines whether accepted or rejected. However, BPR Sindang Binaharta Lubuklinggau has not fully implemented the five analyzes. From the results of the author's interviews with the correspondents, there are still considerations such as Character, Capacity and Collateral. 5C analysis can also be assessed from documents on credit analysis (qualitative analysis), BI Cheking results and also approaches to prospective customers.